Central Bank Independence: Reassessing the Measurements. - Forder, J (1999)
Attempts to test the hypothesis that central bank independence lowers inflation have not produced a way of assessing measures of independence. In practice a measure is often treated as good if and only if it confirms the hypothesis. The most well known measures are much less similar than is often supposed, further suggesting that there is no agreed, empirical and measurable content to the notion of independence. One is forced to the conclusion that attempts to test the independence hypothesis have failed to follow scientific procedures, and therefore that there is no empirical support for it.